Developing Students' Attitudes of Responsibility through Islamic Cultural History (SKI) Learning Based on Story Narratives - Nur Azizah Zulkifli; Nur Hasanah; Zakiah Nasution (Darul Yasin Al Sys, 2026)
Character education plays a critical role in fostering students’ responsibility; however, instructional approaches capable of meaningfully integrating moral values into classroom learning remain essential. This study aims to analyze the development of students’ responsibility through story-based Islamic Cultural History (SKI) learning, which presents exemplary values embodied by Islamic figures as models for students’ everyday conduct. The study employed a qualitative descriptive method, with data collected through observations, interviews, and documentation and analyzed through data reduction, data display, and conclusion drawing. The findings indicate that story-based SKI learning facilitates the internalization of exemplary values and contributes to the development of students’ responsibility. This development was reflected in greater discipline during learning activities, increased awareness of completing assignments on time, and more responsible behavior in both classroom activities and daily school life. Story-based learning also strengthened students’ emotional engagement, enabling them to understand and apply moral values more effectively. The effectiveness of this approach was supported by teachers’ ability to narrate stories engagingly, the use of varied instructional media, and a conducive school environment. Nevertheless, its implementation was constrained by limited instructional time, differences in students’ characteristics, and insufficient supporting media. The study concludes that story-based SKI learning provides a relevant pedagogical approach to integrating historical knowledge with responsibility development. These findings offer practical implications for Islamic education teachers seeking to design engaging, value-oriented learning that connects exemplary historical narratives with students’ everyday behavior.